The evolution of racket sport science—a personal reflection - Lees, A. (German Journal of Exercise and Sport Research, 2019)
The purpose of this paper is to review and reflect on the developments and directions of racket sport science over the last half century or so. It is not a review in the conventional scientific sense—this would be too large an undertaking—but a personal view, the reflection of a career in sports science and of a contributor to racket sport science.